Usage of Social Media Tools in Teaching and Learning and Its Influence on Students Engagement, Knowledge Sharing and Academic Performance - Abdul Hamid, Nor Aziati (Research in Management of Technology and Business, 2020)
This study aims to identify the social media usage and its influence on student engagement, knowledge sharing and academic performance. The gaining acceptance of social media platform’s in education as one of teaching and learning aids has derived much interest among researchers especially towards academic achievement. Limited studies have been focusing on the educators’ readiness, adoption or rejection in integrating social media tools into their courses, besides the perceived effectiveness of social media toward students’ learning. For quantitative method, data were collected using online survey. The respondents were conveniently sampled among UTHM students from all technical and non-technical faculties to examine the level of their engagement and knowledge sharing using social media platform. For qualitative approach, semi structured interview session was conducted among UTHM academician that use any types of online learning platforms in teaching to examine their instructional design strategies and related issues pertaining to online learning. The results found that social media usage in learning positively influence on student engagement, knowledge sharing and also academic performance. For instructional design strategies, the instructors basically chose scenario based and demonstration-practice method in teaching. This study is used to seek the potential benefits of social media in university and help Centre for Academic Development and Training (CAD) to utilize any suitable online learning platform that can attract students participate in class besides improves academic performance of the students.